-3(t-4)-(t+9)=3

Simple and best practice solution for -3(t-4)-(t+9)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(t-4)-(t+9)=3 equation:


Simplifying
-3(t + -4) + -1(t + 9) = 3

Reorder the terms:
-3(-4 + t) + -1(t + 9) = 3
(-4 * -3 + t * -3) + -1(t + 9) = 3
(12 + -3t) + -1(t + 9) = 3

Reorder the terms:
12 + -3t + -1(9 + t) = 3
12 + -3t + (9 * -1 + t * -1) = 3
12 + -3t + (-9 + -1t) = 3

Reorder the terms:
12 + -9 + -3t + -1t = 3

Combine like terms: 12 + -9 = 3
3 + -3t + -1t = 3

Combine like terms: -3t + -1t = -4t
3 + -4t = 3

Add '-3' to each side of the equation.
3 + -3 + -4t = 3 + -3

Combine like terms: 3 + -3 = 0
0 + -4t = 3 + -3
-4t = 3 + -3

Combine like terms: 3 + -3 = 0
-4t = 0

Solving
-4t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '-4'.
t = 0

Simplifying
t = 0

See similar equations:

| 1.5-2.5x+8.5=-2.5 | | 15n-3/2=6 | | 44=122 | | 7-2-(-8)-11= | | -8(t-3)-(t+1)=8 | | -14+58-(-13)-16= | | 5w^2=5w-10 | | 5+8(x-1)=5-2(x-9) | | 36+(-52)+31= | | -15+12+(-27)+25= | | y=9(0)+3 | | 5+5(x-6)=6-6(x-3) | | y=9(3)+3 | | 2+4=-6 | | y=93+3 | | h=-4t^2+20t+7 | | 16x^2+50x+3.5=0 | | 3x^2-34x=-4x^2-7x-18 | | ln(9x+4)-lnx=ln(10) | | log(6x-5)+log(x+5)=1 | | 96=17x-5x | | 2x^2+5x+9=0 | | 9u+8/5+5u+5/4=12 | | 10x^2+25x+45=0 | | 3x+2x+4x=15+8 | | -5(a-2b+3a-2b)=2(-2-3b) | | 0=9x+3 | | 3y^2-10y+7=0 | | 9q+15q= | | =.2x^2-2.4x+.2 | | 6(k-3)-5(k+2)= | | =2x^2-4x+9 |

Equations solver categories